The effects of meteorological factors and Alternaria spore concentrations on children sensitised to Alternaria - Kilic, M.; Altintas, D. Ufuk; Yilmaz, M.; Kendirli, S. Gueneser; Karakoc, G. Bingoel; Taskin, E.; Pinar, N. M. (Elsevier Doyma Sl, 2010)
Background: Alternaria is the most important fungal species belonging to the class Deuteromycetes which causes allergic respiratory diseases. The fungus pattern often shows a pronounced seasonal periodicity and with fluctuations related to meteorological conditions. In this study, we aimed to investigate the effect of outdoor Alternaria spore concentrations on monthly lung function tests, symptoms, and medication scores in children sensitised only to Alternaria. Additionally, we planned to determine the Alternaria spores of the outdoor environment in Adana, with special respect to their relationships with meteorological conditions and their seasonal changes. Methods: Twenty-five patients with a clinical diagnosis of asthma and/or rhinitis sensitised only to Alternaria were enrolled in the prospective study. Meteorological data and outdoor samples of airborne fungi were obtained between November 2006 and October 2007. Results: The outdoor Alternaria spore concentrations were significantly correlated with the monthly average temperature (r=0.626, p=0.03) and monthly average barometric pressure (r=-0.613, p=0.03). Similarly, the outdoor Alternaria spore concentrations were significantly correlated with mean monthly asthma medication score (r=0.599, p=0.04), value monthly PEF (r=-0.737, p=0.006), value monthly FEF25-75% (r=-0.914, p=0.0001) and, variation in PEF (r=0.901, p=0.0001). Conclusions: The atmospheric concentration of Alternaria spores are markedly affected by meteorological factors such as air temperatures and barometric pressures. In hypersensitive patients, Alternaria spores can induce decreases in respiratory functions and development of allergic symptoms between May and September, being especially more influential in August. (C) 2009 SEICAP. Published by Elsevier Espana, S.L. All rights reserved.
Keywords: Alternaria; Meteorological conditions; Rhinitis; Asthma; Children